Certain Analyses on Static Compensated Voltage and Frequency Modulation in the Wind Energy System using the Solar PV Interface QZSI Impedance Source Network - Partheeban. M, Ramachandran. S, Raja. M, Gowrishankar. C, Deivamani. G, Rathinam. A (Mathematical Statistician and Engineering Applications, 2023)
The generation of electricity from wind and solar Photovoltaic (PV) systems is entirely dependent on weather conditions and variable nature causes output will sag and swell. As a reason, the requirement for efficient techniques for energy transmission and distribution networks is becoming increasingly critical. In the proposed system Quasi Impedance Source Inverter (QZSI)-based Static Compensator (STATCOM), is used to improve power quality in hybrid distributed power generating systems. The Photovoltaic (PV), Wind Energy Conversion System (WECS), and battery energy storage system are all components of the distributed power generating system.DFIG is made up of stator windings that are directly linked to the fixed frequency and voltage-based converters that are allowed directly in rotor windings. The phrase doubly fed refers to the fact that the stator voltage is obtained from the mains even though the rotor voltage is generated by the power converter.Each unit is linked to a DC Bus parallel to the battery to provide backup power. All three units are linked in series by multiple programmable switches for PWM, which are controlled by a DC voltage regulator of an MPPT (Maximum Power Point Tracking) Based Swarm Integral Neural Controller technique controller. The module is a series connection of two or more sources with high-frequency switches attached between the source converters to obtain varied voltage levels as required by the application.